It is 32 because highest number subtracted by lowest
Answer:
x=10
Step-by-step explanation:
I'm assuming you needed to solve for x. Here is how you do it:
first, divide both sides by 4/5 to get x by itself.
this will give you x=8 divided by 4/5.
To solve 8 divided by 4/5 you do keep switch flip.
keep the first number (8), switch the sign (division to multiplication), and flip the other fraction (4/5 to 5/4) then you can just multiply across the top (8/1 *5/4) which equals 40/4. This simplified is 10
Answer:
7.16666666667. hope this helps
Step-by-step explanation:
- Zombie
ANSWER
The correct answer is D.
![\sum_{n=1} ^{6} (n - 3) = ( - 2) + ( - 1) + (0) + (1) + (2) + (3) = 3](https://tex.z-dn.net/?f=%20%5Csum_%7Bn%3D1%7D%20%5E%7B6%7D%20%28n%20-%203%29%20%3D%20%28%20-%202%29%20%2B%20%28%20-%201%29%20%2B%20%280%29%20%2B%20%281%29%20%2B%20%282%29%20%2B%20%283%29%20%3D%203)
EXPLANATION
The given expression is
![\sum_{n=1} ^{6} (n - 3)](https://tex.z-dn.net/?f=%20%5Csum_%7Bn%3D1%7D%20%5E%7B6%7D%20%28n%20-%203%29)
The symbol means summation.
So we need to substitute
![n=1,n=2,n=3,n=4,n=5, \:and\:n=6](https://tex.z-dn.net/?f=n%3D1%2Cn%3D2%2Cn%3D3%2Cn%3D4%2Cn%3D5%2C%20%5C%3Aand%5C%3An%3D6)
into the formula and add all to get,
![\sum_{n=1} ^{6} (n - 3) = (1 - 3) + (2 - 3) + (3- 3) + (4 - 3) + (5 - 3) + (6 - 3)](https://tex.z-dn.net/?f=%20%5Csum_%7Bn%3D1%7D%20%5E%7B6%7D%20%28n%20-%203%29%20%3D%20%281%20-%203%29%20%2B%20%282%20-%203%29%20%2B%20%283-%203%29%20%2B%20%284%20-%203%29%20%2B%20%285%20-%203%29%20%2B%20%286%20-%203%29)
We simplify to obtain,
![\sum_{n=1} ^{6} (n - 3) = ( - 2) + ( - 1) + (0) + (1) + (2) + (3) = 3](https://tex.z-dn.net/?f=%20%5Csum_%7Bn%3D1%7D%20%5E%7B6%7D%20%28n%20-%203%29%20%3D%20%28%20-%202%29%20%2B%20%28%20-%201%29%20%2B%20%280%29%20%2B%20%281%29%20%2B%20%282%29%20%2B%20%283%29%20%3D%203)
The correct answer is D